Role of Software Quality Assurance in Software Development (International Journal of Engineering and Computer Science, 2017)
Software industry is one of the leading one among other industries. The scope of a software application is increasing day by day and also the dependency over the software application is increasing. We can see software usage in medical laboratories, pharmaceutical laboratories, maintaining database of different organization, facilitating the sports person by visualizing their performance etc. So it is the prime responsibility of software industry to provide efficient and durable facility to its customers. This is a well known fact that every organization makes its mind earlier to achieve profit in their business and same here in the software industries. This paper represents the various aspects of the scope of the software application by impacting on the software quality.